Media Pembelajaran Interaktif Pasang Aksara Bali Pada LMS Melajah.id Kelas X SMKN 1 Amlapura - I Made Dwi Sutanegara; I Nyoman Linggih; I Gede Suwantana (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
Abstract The online learning process that has been carried out at SMKN 1 Amlapura is less than optimal, it is proven that there is a lack of understanding to understand the material of Balinese script pairs in class X students. One of the factors causing the low understanding of students is the use of learning media during online learning. The interactive learning media of Balinese script is a two-way media which is expected to increase the understanding of class X students of SMKN 1 Amlapura. The problems of this research are (1) what is the cause of the use of interactive learning media using Balinese script in LMS melajah.id class X SMKN 1 Amlapura? (2) How is the process of using interactive learning media to install Balinese script in LMS melajah.id class X SMKN 1 Amlapura? (3) What are the implications of the interactive learning media of Balinese script on LMS melajah.id? This study concludes that the causes of using Balinese script interactive learning media are; (1) alternatives during a pandemic, (2) encouraging students to study independently. (3) access to learning materials is very flexible (4) costs are cheaper, (5) makes it easier to analyze student-processed data (6) learning variations are not monotonous, (7) learning media in the era of the industrial revolution 4.0. The process of using interactive learning media for Balinese script includes three stages, namely: (1) the planning stage, the implementation stage, and the evaluation stage. The application of interactive learning media with Balinese script has implications for (1) to Balinese language teachers (2) to students (3) to school management